Optimasi Laju Alir Tri-Ethylene Glycol terhadap Efisiensi Penyerapan Air pada Kolom Absorbsi Di PT. Pertamina Hulu Energi - Andri Riski Maulizar; Alfian Putra; Muhammad Yunus (Politeknik Negeri Lhokseumawe, 2023)
Absorption was a separation process between gas fluids using liquid fluid media. The glycol contactor aims to separate the water content contained in the gas using tri-ethylene glycol media with process conditions at a pressure of 795-810 psi and a temperature of 85-110 oF. The contact process between fluids is assisted by the Intalox Saddle type packing which aims to maximize the contact process between fluids and it is hoped that the absorption process that occurs can be maximized. Tri-ethylene glycol which has absorbed the water content in the gas is regenerated in the glycol burner. This analysis used 4 packing variables (Raschig Rings, Pall Rings Plastic, Berl Saddles Ceramic, and Intalox Saddles Ceramic), 5 flow rate variables (1600, 1800, 2000, 2200, and 2400 BPD) and this analysis use the Hysys simulation program. Based on these variables, the absorption efficiency analysis results are obtained in the range of 93-94%, and the flooding percentage is 21-36%. It can be concluded that the type of packing is very influential on the percentage of flooding. Pall Ring Plastic was the type of packing with the lowest flooding percentage. According to research, lower flow rates increase the efficiency of H2O absorption.